Last updated at Sept. 8, 2021 by Teachoo

Transcript

Example 5 Simplify the expressions and evaluate them as directed: (i) ๐ฅ (๐ฅโ3)+2 for ๐ฅ=1 ๐ฅ (๐ฅโ3)+2=๐ฅร๐ฅโ๐ฅร3+2 =๐ฅ^2โ3๐ฅ+2 For x = 1 Putting x = 1 in expression ๐ฅ^2โ3๐ฅ+2 = 1^2โ3ร1+2 = 1โ3+2 = (1+2)โ3 = 3โ3 = ๐

Examples

Example 1
Important

Example 2 Important

Example 3

Example 4

Example 5 (i) You are here

Example 5 (ii)

Example 6 (i) Important

Example 6 (ii)

Example 7 Important

Example 8 (i)

Example 8 (ii)

Example 9 (i) Important

Example 9 (ii)

Example 10 Important

Example 11 (i)

Example 11 (ii)

Example 12 (i)

Example 12 (ii)

Example 13 (i)

Example 13 (ii)

Example 13 (iii)

Example 14 (i)

Example 14 (ii)

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.